2020
DOI: 10.3390/en13226050
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Analysis of Timber Windows with Different Wood Species and Anatomical Direction

Abstract: When assessing the hygrothermal performance of timber windows, it is important to apply the unique thermal conductivity of wood by each wood species as well as an anatomical direction within the same material as they affect the performance and long-term durability of products. A series of heat transfer analyses of window frames using THERM and WINDOW along with measurements on the thermal conductivity of five hardwoods using laser flash apparatus (LFA) was performed to compare and evaluate heat transmittance (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…± St. Dev. = 0.18 ± 0.06)[18,124,125]. For wood chars, the situation is much more difficult because only a few studies provided those parameters, and that includes only for a few species (Longitudinal (n = 13) -Min.…”
mentioning
confidence: 99%
“…± St. Dev. = 0.18 ± 0.06)[18,124,125]. For wood chars, the situation is much more difficult because only a few studies provided those parameters, and that includes only for a few species (Longitudinal (n = 13) -Min.…”
mentioning
confidence: 99%
“…Recently, most of the research has focused on particleboard materials and the optimization of wood performance [5][6][7][8][9][10]. Moslemi et al found that cellulose nanofibers can be extracted from rice straw and mixed with urea-formaldehyde adhesive for the production of medium density fiberboard (MDF) to optimize the rupture modulus, elastic modulus and internal bond strength of the MDF [11].…”
Section: Introductionmentioning
confidence: 99%